The benefits of participating in an industrial cluster from the perspective of the firm - Neil Reid; Michael C. Carroll (European Regional Science Association (ERSA), 2012)
The purpose of this presentation is to discuss the initial measures that have been developed to evaluate the success of an industrial cluster that is focused on the greenhouse industry in northwest Ohio, USA. The firms that make up the core of this cluster are family-owned SMEs that are in the mature stage of the industrial life cycle. As such they are facing some significant competitive challenges that are threatening their future viability. Researchers from three local universities have been working with firms in the cluster to help them address these competitive challenges collectively. Success is defined as the benefits that the cluster has generated for the participating firms and the local industry. An assessment of the impact of the cluster on the regional economy is outside the domain of this presentation. The work reported in this paper is only the beginning phases of a longer-term, on-going effort to track the progress and success of the cluster.
Keywords: 330